The Mahabharata : 2. The Book Of The Assembly Hall 3. The Book Of The Forest / / penerjemah dan editor, J.A.B. Van Buitenen - Buitenen, J.A.B. Van (The University Of Chicago Press, 1975)
xi, 465 hlm : ilus. ; 24 cm